Preliminary study of screen–printed gold electrode for H2O2 sensor based on electrochemiluminescence of luminol - Syukur, Junjunan Muhammad; Sanjaya, Afiten Rahmin; Rahmawati, Isnaini; Ridwan, Muhammad (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Hydrogen peroxide (H2O2) is mostly used in the water and dairy industries for sterilization and preservation purposes. However, excessive H2O2 residues in milk and tap water pose a health risk. Therefore, accurate measurement of H2O2 residue is essential. Methods: This study explores the potential of a screen–printed gold electrode (SPGE) as a sensor for H2O2 sensor using the electrogenerated chemiluminescence (ECL) method of luminol in the electrolyte of phosphate buffer solution (PBS) under alkaline condition (pH of 9). Findings: The detection of H2O2 was achieved a linear calibration equation of y = 0.0215[H2O2] + 0.2006 within a concentration range of 0.5 to 200 µM (R2 = 0.9998), demonstrating reliable ECL measurements. Conclusion: The analytical performance evaluation of H2O2 sensor exhibited a low limit of detection (LOD) of 3.06 µM, a limit of quantification (LOQ) of 10.20 µM, and good measurement repeatability, with a relative standard deviation (%RSD) of 6.03%, which is below ⅔ of the Horwitz coefficient of variation (9.85%). Unmodified SPGE offers simplicity, ease of use, a stable surface, and good conductivity while maintaining excellent performance. Novelty/Originality of this article: The application of the ECL method on SPGE for H2O2 detection offers excellent analytical performance, making it a promising approach for monitoring H2O2 residues in the water and dairy industries, with a recovery from 83.83 to 106.01%.